2012
DOI: 10.1109/tmech.2011.2108664
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for Modeling Piezoresistive Force Sensors Based on Semiconductive Polymer Composites

Abstract: Semi-conductive polymer composites are used in a wide range of sensors, measurement devices. This paper discusses the development of a model and a new theoretical formulation for predicting piezoresistive behavior in semi-conductive polymer composites including their creep behavior and contact resistance. The relationship between electrical resistance and force applied to the piezoresistive force sensor can be predicted by using the proposed theoretical formulation. In order to verify the proposed formulation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(110 citation statements)
references
References 33 publications
6
104
0
Order By: Relevance
“…This approach was moved forward for FSRs in [31], where (11) and (12) are taken into account. This analysis complements former approaches [6,8,9] where just (10) was embraced. Journal of Sensors where e is the electron's charge, m its mass, φ 0 is the height of the potential barrier, and the constant ℏ = h/2π, being h the Planck's constant.…”
Section: Consideration Of the Proposed Approach In The Simmons' Modelsupporting
confidence: 69%
See 3 more Smart Citations
“…This approach was moved forward for FSRs in [31], where (11) and (12) are taken into account. This analysis complements former approaches [6,8,9] where just (10) was embraced. Journal of Sensors where e is the electron's charge, m its mass, φ 0 is the height of the potential barrier, and the constant ℏ = h/2π, being h the Planck's constant.…”
Section: Consideration Of the Proposed Approach In The Simmons' Modelsupporting
confidence: 69%
“…It is straightforward to understand that u = V − R C I, but it has been already stated that R C is a function of stress. This is R C = R C σ [8,32,33]. Therefore, u is also a function of stress u = u σ and this makes the current density J highly dependent on stress.…”
Section: Consideration Of the Proposed Approach In The Simmons' Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors' proposed model imposes a voltage-dependent behavior for the tunneling conduction of FSRs; this is radically different from well-known models in the literature [6,25,26]. The authors' proposed model has demonstrated its validity by predicting-up to some extent-the sensitivity degradation of Conductive Polymer Composites.…”
Section: Review Of the Underlying Physics And Important Definitions Omentioning
confidence: 86%